The potential roles of cell migration and extra-cellular matrix interactions in Dupuytren’s disease progression and recurrence - Vi, Linda (Med Hypotheses, 2009)
Dupuytren’s disease is a pathological condition of the palmar fascia characterized by the formation of contractile disease cords that result in permanent finger contracture. This condition is believed to progress from a myofibroblast-rich nodule in the early clinical stages of the disease to a contractile disease cord spanning a portion of the fascia, leading to contracture of one or more digits. The mechanism(s) by which this disease progresses from a nodule to a collagenous disease cord are poorly understood. Here, we discuss two possible models of disease progression. Firstly, disease progression might be mediated by the proliferation and outward migration of disease cells from within the nodule to populate the adjacent palmar fascia, resulting in a disease cord containing contractile cells derived from the nodule itself. Alternatively, nodular cells may secrete disease-associated factors into the surrounding extra-cellular matrix, thereby altering its composition and triggering quiescent, phenotypically normal cells in the adjacent palmar fascia to take on a proliferative and contractile phenotype. Based on the available evidence and the current state of knowledge of myofibroblast biology, we hypothesize that extra-cellular matrix interactions resulting in conversion of adjacent palmar fascia cells to a disease phenotype is more likely than cell migration from the nodule. Understanding the mechanisms of Dupuytren’s disease progression will assist in the development of effective therapeutic interventions to address the high clinical recurrence rate of this condition.